Blocking landing techniques in volleyball and the possible association with anterior cruciate ligament injury - Zahradnik, D.; Jandacka, D.; Holcapek, M.; Farana, R.; Uchytil, J.; Hamill, J. (Journal of Sports Sciences, 2018)
The number and type of landings performed after blocking during volleyball matches has been related to the potential risk of ACL injury. The aim of the present study was to determine whether gender affects the frequency of specific blocking landing techniques with potential risk of ACL injury from the perspective of foot contact and subsequent movement after the block used by volleyball players during competitive matches. Three matches involving four female volleyball teams (fourteen sets) and three matches involving four male volleyball teams (thirteen sets) in the Czech Republic were analyzed for this study. A Pearson chi-square test of independence was used to detect the relationship between gender and different blocking techniques. The results of the present study showed that gender affected single-leg landings with subsequent movement in lateral direction and double-leg landings. Although the total number of landings was lower for male athletes than for female athletes, a larger portion of male athletes demonstrated single leg landings with a subsequent movement than female athletes. Single leg landings with a subsequent movement have a higher potential risk of ACL injury.